2008
DOI: 10.1089/jmf.2007.0530
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Properties of Frondoside A, a Major Triterpene Glycoside from the North Atlantic Commercially Harvested Sea Cucumber Cucumaria frondosa

Abstract: Frondoside A, a major triterpene glycoside from North Atlantic commercially harvested sea cucumber Cucumaria frondosa, possesses strong immunomodulatory properties in subtoxic doses. Frondoside A stimulates lysosomal activity of mouse macrophages in vivo at a maximal effective stimulatory dose of 0.2 microg per mouse and is maintained over 10 days. This glycoside also shows a 30% stimulation of lysosomal activity in mouse macrophages in vitro at concentrations of 0.1-0.38 microg/mL. Frondoside A enhances macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 16 publications
1
69
0
Order By: Relevance
“…For instance, Frondoside A 43 , reported as the major triterpene glycoside from sea cucumber Cucumaria frondosa, possesses immunomodulatory properties [124]. This group suggested that Frondoside A 43 induced prolonged lysosomal activity of mouse macrophages in vivo and in vitro with different concentrations, and stimulated the phagocytosis process of macrophages.…”
Section: Immunomodulatory Properties Of Acetylated Saponinsmentioning
confidence: 99%
“…For instance, Frondoside A 43 , reported as the major triterpene glycoside from sea cucumber Cucumaria frondosa, possesses immunomodulatory properties [124]. This group suggested that Frondoside A 43 induced prolonged lysosomal activity of mouse macrophages in vivo and in vitro with different concentrations, and stimulated the phagocytosis process of macrophages.…”
Section: Immunomodulatory Properties Of Acetylated Saponinsmentioning
confidence: 99%
“…The reduction primarily occurs through growth inhibition and induction of apoptosis (12). Further, Collin et al demonstrated that Frondoside A, a component of Frondanol ® A5, inhibited microtubule formation in an angiogenesis assay, and also stimulated innate immunity in vivo (33-34). Dietary supplementation of Frondanol ® A5 in combination with other natural agents enhanced its anti-inflammatory properties (35).…”
Section: Discussionmentioning
confidence: 99%
“…In a typical procedure, frozen mixed intestines and frozen mixed body walls from treatment and control groups were ground well to powder with a cold mortar and pestle, and kept in a liquid nitrogen bath in a styrofoam box during the entire procedure [13]. Protein concentration was determined by the Bradford colorimetric method (Bio-Rad) following standard protocol.…”
Section: Total Protein Extraction and Quantificationmentioning
confidence: 99%
“…A total of six samples were obtained for each group in the end. The M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 7 samples were homogenized with a cold mortar and pestle in a liquid nitrogen bath [13]. And total RNA was extracted using RNAiso Plus (TaKaRa Bio Group, DaLian).…”
Section: Verification Of Differentially Expressed Proteinsmentioning
confidence: 99%